2013
DOI: 10.4049/jimmunol.1202122
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Negatively Regulates Dendritic Cell Production of IL-23/IL-17–Axis Cytokines in Infection by Histoplasma capsulatum

Abstract: Galectin-3 (gal3) is known for its immunoregulatory functions in infectious, autoimmune, and inflammatory diseases. However, little is known about its regulatory role in the host's IL-17A response to infection. Using a mouse model of histoplasmosis in which both Th1 and Th17 responses contribute to fungal clearance, we investigated how gal3 regulates IL-17A responses. Our study showed that Histoplasma infection induced gal3−/− dendritic cells to produce significantly higher levels of IL-23, TGF-β1, and IL-1β t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 48 publications
(61 reference statements)
1
66
1
Order By: Relevance
“…Using this concept, Wu et al demonstrated that gal-3 deficient mice cleared Histoplasma more efficiently than wild type mice, and that the DCs from the mutant mice produced higher levels of IL-23, TGF-b1, and IL-1b compared to the control mice. 85 H. capsulatum also induced higher levels of IL-17A and greater percentages of Th17 cells, but lower levels of IFN-g, IL-12 as well as a lower percentages of Th1 cells. The results of this study support the role of gal-3 in negatively regulating host IL-17 responses to Histoplasma by impeding IL-23/IL-17-axis cytokine production by DCs.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Using this concept, Wu et al demonstrated that gal-3 deficient mice cleared Histoplasma more efficiently than wild type mice, and that the DCs from the mutant mice produced higher levels of IL-23, TGF-b1, and IL-1b compared to the control mice. 85 H. capsulatum also induced higher levels of IL-17A and greater percentages of Th17 cells, but lower levels of IFN-g, IL-12 as well as a lower percentages of Th1 cells. The results of this study support the role of gal-3 in negatively regulating host IL-17 responses to Histoplasma by impeding IL-23/IL-17-axis cytokine production by DCs.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…The results of this study support the role of gal-3 in negatively regulating host IL-17 responses to Histoplasma by impeding IL-23/IL-17-axis cytokine production by DCs. 85 Paracoccidioides brasiliensis Paracoccidioidomycosis (PCM) is caused by a complex group of fungi comprising 4 distinct phylogenetic lineages (PS2, PS3, S1 and Pb01-like). The first 3 lineages are speciated as Paracoccidioides brasiliensis whereas Pb01 is morphologically and genetically distinct and is designated as Paracoccidioides lutzii.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…Reported data suggest that Galectin-3 suppresses IFN-γ production by antigen-specific CD8 + T cells in vitro (95). Further, dendritic cells lacking the Galectin-3 gene have been shown to increase both T-cell numbers and cytokine production in helminthic infections and promote an effective Th17 immune response (107,108). Altogether, it appears that Galectin-3 is involved in the tuning of acquired immunity against tumours by determining the cytokine milieu in the tumour microenvironment.…”
Section: Foxp3mentioning
confidence: 99%
“…It has been suggested that Galectin-3 also influences the strength of antigen activation in dendritic cells (21,22) and controls acquired immunity, including both T-helper cell 1 (Th1) (23,24) and T-helper cell 2 (Th2) responses (21,25) depending on the context of the host immune response. Along with its role in inflammation and immune responses in noninfectious conditions, Galectin-3 can detect certain microorganisms by binding specific carbohydrate structures of glycoproteins and glycolipids from many pathogens (26).…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially explained by the enhanced production of IL-23 cytokines observed in infected galectin-3 ¡/¡ dendritic cells. 90 A C. albicans strain defective in the b-1,2-mannosyltransferase Bmt1 and a strain with no b-M (bmt1 bmt2 bmt5 mutant) exhibit a similar or reduced virulence (respectively) in galectin-3 ¡/¡ mice compared to its wild type counterpart. 82 We demonstrate here that the avirulent phenotype of cek1 mutants 36 is not caused by the absence of galectin-3, despite the significant reorganization of the cell wall which is reflected in the epitopes that are recognized by this receptor in the surface of the cell.…”
mentioning
confidence: 99%